Debating the Saints’ Cult in the Age of Gregory the Great. By Matthew Dal Santo - Cameron, Averil (2014)
Near the end of the sixth century, a priest in Constantinople called Eustratius, the author of an encomiastic Life of Eutychius, the recently deceased patriarch, and later of a Greek version of the Life of the female Persian martyr Golindouch, composed a treatise on the state of souls after death. In it he defended the belief in the continued activity of souls after death against the idea that souls fell into a kind of sleep or, more radically, the theory that they ceased to exist altogether. In the 590s Gregory the Great also argued for the activity of souls after death in his fourth Dialogue on the Miracles of the Italian Fathers, a work arguing more broadly for the efficacy of saints in producing miracles.
Keywords: Rezension